DOES SUSTAINABILITY REPORT DISCLOSURE MATTER ON CORPORATE PERFORMANCE? - Triwacananingrum, Wijaya; Silphianie (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
The issue of sustainability is currently emerging, although there still needs to be more empirical evidence explaining its contribution to company performance. Therefore, this research examines the effect of sustainability report disclosure on company performance. Sustainability report disclosure is measured using the Sustainability Report Disclosure Index (SRDI), while company performance is proxied by Return on Assets (ROA) and Sustainable Development Goals (SDGs). Multiple linear regression analysis tests were conducted on 45 sample companies, with 126 observations on companies listed on the Indonesia Stock Exchange during 2019-2021. The research results reveal that disclosure of sustainability reports does not significantly influence the company's financial and non-financial performance. These results indicate that limited disclosure of corporate sustainability reports has implications for economic instability, especially during the pandemic and the company's lack of contribution to the 17 Sustainable Development Goals (SDGs).